Influence of salt structures on the location of glacial valleys within the Pripyat Trough (Belarus) - Komarovskiy, Michail E. (Journal of the Belarusian State University. Geography and Geology, 2020)
It was found that glacial valleys in the Pripyat Trough are connected with the location of the halokinetic structures of the Upper-Famennian salt strata. Valleys were noticed over salt structures, which developed during the Quaternary. The most part of valleys is over salt diapires, pillows and swells, rarer they occur within synclinales and troughs. Within local anticlinales valleys focus mainly in its tops and limbs, which have incline down glacier. Within salt synclinales valleys lie over its axis and limbs, which are connected with adjacent anticlinales. The most typical regularities of the glacial valleys localization within the salt structures is their close connection with active fault systems. These faults propagate upwards from the tops and flanks of diapires across the Upper-Famennian and supra-salt overburden into the Quaternary, where underlie the valleys. The developing of salt structures and faults during the Narev and Dnieper glaciations created weakness zones in glacial bed that facilitated erosion by the glaciers and subglacial melt water.